A confidence map based damage assessment approach using pulsed thermographic inspection. (January 2018) - Zhao, Yifan; Addepalli, Sri; Sirikham, Adisorn; Roy, Rajkumar
Abstract: In the context of non-destructive testing, quantification of uncertainty caused by various factors such as inspection technique, testing environment and the operator is important and challenge. This paper introduces a concept of contour-based confidence map and an application framework for pulsed thermography that offers enhanced flexibility and reliability of inspection. This approach has been successfully applied to detect three flat-bottom holes of diameter 32, 16 and 8 mm drilled onto a 5 mm thick aluminium plate with a high accuracy of damage detection (R > 0.97). Its suitability and effectiveness in assessing impact damage occurring in composites have also been demonstrated. Highlights: A contour-based confidence map for enhanced damage assessment has been introduced. An APTC method for improved temperature contrast for multiple defects is proposed. A confidence map based thermography inspection framework has been introduced.